TINJAUAN KONSTITUSIONAL TERHADAP PROSEDUR LEGISLASI DAN SUPREMASI SIPIL DALAM REVISI UNDANG-UNDANG TENTARA NASIONAL INDONESIA - Romanti, Vita Ayu; Pawestri, Eki; Sari, Mia Indah Puspita (Universitas Labuhanbatu, 2025)
This study aims to evaluate the conformity of the legislative process and the substantive content of Law Number 3 of 2025, which amends Law Number 34 of 2004 concerning the Indonesian National Armed Forces (TNI), with the principles of proper law-making, the rule of law, and civilian supremacy as enshrined in the 1945 Constitution of the Republic of Indonesia. Using a normative juridical approach, the research finds that the legislative process for the TNI Law revision did not fully adhere to the principles of legality, transparency, and public participation, as regulated by Law Number 12 of 2011 in conjunction with Law Number 13 of 2022. The substance of the revision also raises concerns regarding the principles of civilian supremacy and the rule of law, particularly due to the expanded role of the TNI in civilian affairs without sufficient oversight and the allowance of active military officers to occupy strategic civil positions without retirement mechanisms. These findings indicate formal defects in the TNI Law revision that may threaten democratic principles, accountability, and the integrity of the national legal system.This research contributes to the development of constitutional law studies and strengthening the principle of civil supremacy in the legislative process. Keywords: TNI, civilian supremacy, legislation, democracy